Challenges Facing Developers of Diagnostic Tests for Sepsis: A Report From Sepsis Alliance and the Infection Management and Sepsis Collaborative Community - Michael T. McCurdy, MD, FCCM; Timothy E. Sweeney, MD, PhD; Debra Foster, BSc; Bobby Reddy, Jr, PhD; Steven Q. Simpson, MD; for Sepsis Alliance and the Infection Management and Sepsis Collaborative Community (IMSCC) Panelists; Sandy Cayo; Matthew Churpek; Shannon Davila; Paul Epner; Jon Glaudemans; Helen Haskell; et al. (Critical Care Explorations)
OBJECTIVES:. To characterize regulatory and clinical adoption challenges to developing host-based sepsis diagnostics and to establish a common framework for stakeholders to work together toward potential solutions to these challenges. DESIGN:. Expert review, structured interviews, and small group discussions with experienced clinicians and experts in diagnostic test development and regulatory issues. SETTING:. A series of large and small group conference calls conducted from January 2023 to September 2024, along with a review of the available evidence and scope of the issue. SUBJECTS:. A collaborative group of multinational and multidisciplinary sepsis-focused patient advocacy groups, academic research groups, regulatory experts, and executives and clinical leaders from private companies assembled by Sepsis Alliance’s Infection Management and Sepsis Collaborative Community. INTERVENTIONS:. The implications of existing regulatory practices surrounding the evaluation of host-based sepsis diagnostics were examined using structured, small group interviews and discussions. The entire expert panel collated the findings of small groups, and consensus was achieved on the most salient points. MEASUREMENTS AND MAIN RESULTS:. For various reasons, current regulatory practices surrounding host-based sepsis diagnostics pose significant challenges to both regulators and product developers in creating optimal clinical tools. The most important barriers to regulatory approval were considered to be: classification of the diagnostic tests’ goals and output, heterogeneity of sepsis presentation and course, and lack of universal definitions of sepsis. Potential solutions to the challenges were informally proposed, but were not explored rigorously at this project phase. CONCLUSIONS:. A collaborative statement was created outlining the challenges of developing diagnostic tests and devices for sepsis, including existing regulatory requirements surrounding host-based sepsis diagnostics and their implications for ultimate clinical deployment. Characterizing these challenges is a necessary first step to establish a common framework for stakeholders to effectively engage in discussions to develop potential solutions.